Effect of a Precompetition and Postcompetition Training Regime on Body Composition of Soccer Players (Baltic Journal of Sport and Health Sciences, 2018)
The purpose of this investigation was to document the body composition elements’ changes, preparing an initialprecompetition and postcompetition training programme of soccer players. Body composition measurements weretaken 10 weeks prior to competition, at 2 hours before competition and 4 weeks after competition period (week 14).There were investigated: body height (BH), body mass (BM), body mass index (BMI), body fat mass (BFM), fat freebody mass (FFBM), fat free body mass index (FFBMI), body water mass (BWM), water free body mass (WFBM), waterfree body mass index (WFBMI). Body mass, the percent age of BFM and BWM at all body mass was calculated usingthe whole body bioelectrical impedance analysis (BIA) with “Tanita” monitor (Japan).Body mass and body composition values of soccer players varied at precompetition, competition and postcompetitionperiods. The decreased body mass at competition period by 8.16% is the result of lost body fat mass and body watermass. Fat free body mass index (FFBMI) and water free body mass index (WFBMI) indicate, that soccer players atprecompetition and competition period did not use lean tissue, that positively related to the restoration of bodycomposition and water balance at postcompetition period.Keywords: body composition, body mass, body fat mass, body water mass.